Pendampingan Penyusunan Laporan Keuangan UMKM Lontar Ukhti Berbasis SAK EMKM untuk Meningkatkan Akuntabilitas dan Keberlanjutan Usaha: Assistance in Preparing Financial Reports for MSME Lontar Ukhti Based on SAK EMKM to Increase Accountability and Business Sustainability - Muh. Fachruddin; Pongsapan, Marchelyn (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the local economy, including the culinary sector that strengthens regional tourism identities. However, financial management issues remain a major barrier to business growth and sustainability. MSME Lontar Ukhti, a home industry producing traditional Fakfak lontar cake established in 2022, faced challenges due to the absence of systematic financial record-keeping, leaving the owner unable to measure precise profits or financial standing. This community service program aimed to assist MSME Lontar Ukhti in implementing simple financial bookkeeping aligned with SAK EMKM standards. The service employed an andragogic approach and experiential learning through practical mentoring, transaction recording, and financial report compilation using Microsoft Excel. The results demonstrate a significant increase in the owner's competence, enabling the establishment of complete financial statements for the January–November 2025 period, comprising the Balance Sheet (Total Assets Rp150,280,000), Income Statement (Net Profit Rp95,955,000), Statement of Changes in Equity, Cash Flow Statement, and Notes to Financial Statements (CALK). This financial accountability empowers the enterprise to make data-driven decisions and enhances readiness for business expansion.